Optimasi Chatbot dengan Pemanfaatan Natural Language Processing - Salamun, Salamun; Aldi Aprialdo; Sukri (Jurnal Komputer Terapan, 2024)
The use of chatbot applications has grown rapidly in areas ranging from customer service to interactive assistance on multiple platforms. In order to improve the quality and responsiveness of chatbots, this research focuses on utilising natural language processing (NLP) as the main method. NLP is a technology that allows for more natural communication between humans and computers and thus allows chatbots to understand and respond to user requests more accurately. The study includes the development of chatbot applications that incorporate the latest NLP techniques, including natural language processing, sentiment analysis, and context understanding. The results show significant improvements in chatbot performance, improved user interaction with the app, and increased user satisfaction levels. The purpose of this study is to ease the work of administrative staff in providing information and make it easier for students and prospective students to get information that exists today. So that providing and getting information becomes easier and more efficient. Data collection is in the form of literature studies, interviews, and observations. Quantitative methods are used in this research process to conduct testing. The system was tested using black box testing successfully and carried out the User Acceptance Test (UAT) by obtaining an average score of 88.6% of student responses with the predicate "strongly agree," which means users are satisfied with this chatbot application. The results of this study prove that chatbot applications using the NLP method can be used to make it easier for students and prospective students to get the information they want.